Identifikasi Penyakit Tanaman Bawang Merah Varietas Bima Menggunakan Metode Forward Chainning Dan Certainty Factor - Anton Maulana Ibrahim; Abdul Rahman (INTECH, 2021)
Among the many causes of crop failure in shallots are pests and diseases, the symptoms of shallots that are attacked by pests are difficult to identify so only experts are able to correctly identify them. Shallots that are attacked by pests can actually be identified from the beginning until harvest, so that prevention and treatment can be done early on. This pest identification expert system documents expert skills into a computer. An expert system for identifying red onion diseases of the Bima Brebes variety was made using the forward chaining method based on the symptoms of the shallot plant. The certainty factor method is used to determine the level of expert confidence. System testing was carried out on 30 farmers and 5 extension workers to observe 12 samples of shallots that were attacked by pests and diseases. The system test results show that the system's accuracy level is 97%.